QUALITY OF LIFE, PERCEIVED STIGMA, ACTIVITY AND PARTICIPATION OF PEOPLE WITH LEPROSY-RELATED DISABILITIES IN SOUTH-EAST NEPAL - Huib Cornielje; Wim van Brakel; Corline Brouwers (Disability, CBR and Inclusive Development)
In Nepal, many people live with leprosy-related disabilities. The objective of this study was to evaluate differences in socio-economic characteristics, quality of life (QOL), perceived stigma, activity and participation among people affected by leprosy as a group and between this group and the general population, and to identify prime determinants of QOL among the leprosy-affected people. People with leprosy-related disabilities (N=100; 54DGI/46DGII) and community controls (N=100) were selected from Morang district, South-East Nepal, using quota sampling. QOL, perceived stigma and participation and activity limitations were measured using the Nepali abbreviated version of the World Health Organisation Quality of Life (WHOQOL) assessment and the Nepali versions of the Jacoby Scale, Participation Scale and Green Pastures Activity Scale (GPAS), respectively. Total QOL, participation and activity levels of people affected by leprosy were worse than those of the general population. Regression analysis showed that the ability to maintain a family, satisfaction with health, vocational training, sex, activity and participation limitations (the latter for QOL only), perceived stigma and living situation (i.e. joint family, type of house) were significantly associated with a deterioration in QOL and higher participation restriction in one or both of the grading groups. There is an urgent need for interventions focused on quick referral of people with leprosy, to minimize the development of visible impairments, and social rehabilitation. The latter can be achieved by creating more public awareness, providing (financial) support for income generating projects and /or vocational training to leprosy- affected people, and by encouraging them to be involved in all community development activities. The current results indicate that such measures would help improve the quality of life of people with leprosy-related disabilities. DOI 10.5463/DCID.v22i1.15